Social Media and Xenophobic Solidarity in Post-colonial Africa (African Human Mobility Review, 2021)
In recent times, there is a resurgence of aggressive consciousness by citizens of mostAfrican countries, firmly fashioned and sustained through social media. Social mediain this way effectively play roles of mobilizing and (re)constructing national identitiesand solidarities in ways that citizens regularly enter into violent confrontations withforeign nationals, often stereotyped as threats to the prosperity of citizens. In someAfrican countries, executive orders have been given by heads of government that sawthe vicious expulsion of millions of foreign nationals. With the advent of distance-andtime-shrinking information and communication technologies, social media platformssuch as Facebook‚ Twitter‚ YouTube and WhatsApp are relied upon in rousing supportfor national interests and in-group solidarity. Through a systematic review of nationalimmigration policies and content analysis of Facebook newsfeeds in selected countriesof East/Central, West and Southern Africa (Zimbabwe, Ethiopia, the Democratic Republicof the Congo (DRC), Nigeria, Somalia, Ghana, Uganda, and South Africa), thispaper examines how social media strengthen in-group solidarities with the attendantconsequences of loss of lives, properties, and inter-state diplomatic relations in postcolonialAfrica. The paper concludes that while encouraging freedom of expressionwithin the continent, social media also bolster freedom to hate as both citizens andforeign nationals become more distrustful of one another, thereby exacerbating competition,rivalry and xenophobia. As citizens exercise their right to voice their opinions,they also actively dehumanize foreign nationals. The paper recommends that kin andfriendship networks should become the sphere within which interventions for antixenophobiacampaigns occur in post-colonial Africa, as these hold the social capital tobridge the divide between citizens and foreign nationals in attempts to achieve peacefulco-existence.